2017
DOI: 10.1038/s41598-017-09955-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional and proteomic analysis of Ceratonova shasta (Cnidaria: Myxozoa) polar capsules reveals adaptations to parasitism

Abstract: Myxozoa is a diverse, speciose group of microscopic parasites, recently placed within the phylum Cnidaria. Myxozoans are highly reduced in size and complexity relative to free-living cnidarians, yet they have retained specialized organelles known as polar capsules, akin to the nematocyst stinging capsules of free-living species. Whereas in free-living cnidarians the stinging capsules are used for prey capture or defense, in myxozoans they have the essential function of initiating the host infection process. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 60 publications
5
42
1
Order By: Relevance
“…However, it is worth noting that the soluble content of the Hydra nematocyst is known to contain ~ 300 proteins [ 13 ] while the shell proteome represents only ~ 100 proteins, including ~ 20 minicollagen genes [ 14 ]. In agreement, the polar capsule proteome of C. shasta is expected to represent mainly shell proteins since C. shasta polar capsules are incapable of injection and do not contain venom proteins [ 17 ].These numbers suggest that the nematocysts shell is composed of about a hundred proteins, among which only minicollagens and nematogalectins have been recognized as core proteins shared by all cnidarian lineages.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, it is worth noting that the soluble content of the Hydra nematocyst is known to contain ~ 300 proteins [ 13 ] while the shell proteome represents only ~ 100 proteins, including ~ 20 minicollagen genes [ 14 ]. In agreement, the polar capsule proteome of C. shasta is expected to represent mainly shell proteins since C. shasta polar capsules are incapable of injection and do not contain venom proteins [ 17 ].These numbers suggest that the nematocysts shell is composed of about a hundred proteins, among which only minicollagens and nematogalectins have been recognized as core proteins shared by all cnidarian lineages.…”
Section: Discussionmentioning
confidence: 95%
“…Thus far, the entire nematocyst proteome, which also include collagenous proteins which form the nematocyst shell, has only been characterized for H. vulgaris [ 14 ] and recently for the myxozoan Ceratonova shasta [ 17 ]. These two studies revealed a difference in protein numbers, with 410 unique proteins in Hydra and only 112 in Ceratonova.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The staining intensity and consistency across the myxozoans examined with these stains suggest a highly acidic, electron‐dense environment within the polar capsules. This may reflect the presence of poly‐gamma‐glutamate, a polymer composed of an electron‐dense matrix that binds cations present in the nematocysts of Cnidarians and potentially the polar capsules of C. shasta (Piriatinskiy et al, 2017; Szczepanek, Cikala, & David, 2002; Weber, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Minicollagens are likely to play a similar role to those in free-living cnidarians providing the high tensile strength needed to facilitate polar filament deployment 59 . In myxozoans this enables spores to attach to hosts.…”
Section: Host-specific Transcription Linked To Parasite Developmentalmentioning
confidence: 99%